Application of Next-Generation Sequencing to Enterobacter Hormaechei Subspecies Analysis during a Neonatal Intensive Care Unit Outbreak - Morhart, Patrick; Gerlach, Roman; Kunz, Caroline; Held, Jürgen; Valenza, Giuseppe; Wölfle, Joachim; Reutter, Heiko Martin; Hanslik, Gregor J.; Fahlbusch, Fabian B. (Children, 2023)
Introduction: The Enterobacter cloacae complex (ECC) species are potential neonatal pathogens, and ECC strains are among the most commonly encountered Enterobacter spp. associated with nosocomial bloodstream infections. Outbreaks caused by ECC can lead to significant morbidity and mortality in susceptible neonates. At the molecular level, ECC exhibits genomic heterogeneity, with six closely related species and subspecies. Genetic variability poses a challenge in accurately identifying outbreaks by determining the clonality of ECC isolates. This difficulty is further compounded by the limitations of the commonly used molecular typing methods, such as pulsed field gel electrophoresis, which do not provide reliable accuracy in distinguishing between ECC strains and can lead to incorrect conclusions. Next-generation sequencing (NGS) offers superior resolution in determining strain relatedness. Therefore, we investigated the clinical pertinence of incorporating NGS into existing bundle measures to enhance patient management during an outbreak of ECC in a level-3 neonatal intensive care unit (NICU) in Germany. Methods: As the standard of care, all neonates on the NICU received weekly microbiological swabs (nasopharyngeal and rectal) and analysis of endotracheal secretion, where feasible. During the 2.5-month outbreak, colonisation with ECC was detected in n = 10 neonates. The phylogenetic relationship and potential antimicrobial resistance genes as well as mobile genetic elements were identified via bacterial whole-genome sequencing (WGS) using Illumina MiSeq followed by in silico data analysis. Results: Although all ECC isolates exhibited almost identical antimicrobial susceptibility patterns, the WGS data revealed the involvement of four different ECC clones. The isolates could be characterised as Enterobacter hormaechei subspecies steigerwaltii (n = 6, clonal), subsp. hoffmannii (n = 3, two clones) and subsp. oharae (n = 1). Despite the collection of environmental samples, no source of this diffuse outbreak could be identified. A new standardised operating procedure was implemented to enhance the management of neonates colonised with MRGN. This collaborative approach involved both parents and medical professionals and successfully prevented further transmission of ECC. Conclusions: Initially, it was believed that the NICU outbreak was caused by a single ECC clone due to the similarity in antibiotic resistance. However, our findings show that antibiotic susceptibility patterns can be misleading in investigating outbreaks of multi-drug-resistant ECC. In contrast, bacterial WGS accurately identified ECC at the clonal level, which significantly helped to delineate the nature of the observed outbreak.
CRIS-Team Scopus Importer:2023-11-03
Keywords: ECC; Enterobacter; MRGN; NGS; NICU; WGS

Comparison of nine different commercially available molecular assays for detection of SARS-CoV-2 RNA. - Eberle, Ute; Wimmer, Clara; Huber, Ingrid; Neubauer-Juric, Antonie; Valenza, Giuseppe; Ackermann, Nikolaus; Sing, Andreas (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
To face the COVID-19 pandemic, the need for fast and reliable diagnostic assays for the detection of SARS-CoV-2 is immense. We describe our laboratory experiences evaluating nine commercially available real-time RT-PCR assays. We found that assays differed considerably in performance and validation before routine use is mandatory.
EVALuna2:519455

Emergence of novel ST1299 vanA lineages as possible cause for the striking rise of vancomycin resistance among invasive strains of Enterococcus faecium at a German university hospital - Valenza, Giuseppe; Eisenberger, David; Voigtländer, Sven; Alsalameh, Rayya; Gerlach, Roman; Koch, Sonja; Kunz, Bernd; Held, Jürgen; Bogdan, Christian (Microbiology Spectrum, 2023)
IMPORTANCE: The proportion of VREfm among all Enterococcus faecium isolated from blood cultures in German hospitals has increased in the period 2015-2020 from 11.9% to 22.3% with a country-wide spread of the clonal lineage ST117/CT71 vanB. In this study, we provided useful information about the genetic diversity of invasive strains of E. faecium. Moreover, our findings confirm the nosocomial spread of novel ST1299 vanA lineages, which recently had a rapid expansion in Austria and the south-eastern part of Germany.
CRIS-Team Scopus Importer:2023-12-29
Keywords: bloodstream Infection; core genome multilocus sequence typing; Enterococcus faecium; ST1299 vanA; vancomycin resistance

High prevalence of the recently identified clonal lineage ST1299/CT3109 vanA among vancomycin-resistant Enterococcus faecium strains isolated from municipal wastewater - Valenza, Giuseppe; Eisenberger, David; Esse, Jan; Held, Jürgen; Lehner-Reindl, Verena; Plaumann, Peter Louis; Ziegler, Tobias; Knauer, Max; Bogdan, Christian; Dudler, Patrick (mSphere, 2024)
Previously, we demonstrated that the majority of vancomycin-resistant Enterococcus faecium (VREfm) strains from in-patients of the University Hospital Erlangen, Germany, belonged to only three clonal lineages, namely ST117/CT71 vanB and two novel ST1299 vanA lineages classified as CT3109 and CT1903. The goal of the current study was (i) to investigate whether VREfm is also detectable in wastewater of the city of Erlangen, (ii) to identify their molecular features, and (iii) to clarify whether VREfm could arise from the community of the city of Erlangen or can be (directly) connected to nosocomial infections in the hospital setting. From April to May 2023, a total of 244 VREfm strains from raw wastewater of the city of Erlangen were analyzed by core genome multilocus sequence typing (cgMLST). Moreover, 20 of them were further investigated for single nucleotide polymorphisms (SNPs). The molecular characterization of the wastewater VREfm strains revealed a high prevalence (27.9%) of the recently identified clonal lineage ST1299/CT3109 vanA, which is mainly characterized by the presence of the tetracycline-resistance determinant tet(M) and the virulence genes pilA and prpA. The SNPs analysis revealed the presence of two major clusters, namely cluster I (≤65 SNPs), which included well-known hospital-adapted vanB clonal lineages such as ST117/CT71 and ST80/CT1065 and cluster II (≤70 SNPs), which were mainly characterized by the lineage ST1299/CT3109 vanA. Based on the concomitant resistance to vancomycin and tetracycline, we propose that ST1299/CT3109 vanA primarily originated and spread outside of hospital settings.IMPORTANCEThis study provides a detailed genomic analysis of vancomycin-resistant Enterococcus faecium (VREfm) strains isolated from municipal wastewater with a particular focus on clonal lineages, antimicrobial resistance, and the presence of virulence genes. The high wastewater prevalence of the recently identified clonal lineage ST1299/CT3109 vanA, which has been previously detected in hospitals, suggests an enormous potential for future spread in Germany.
CRIS-Team Scopus Importer:2024-10-04
Keywords: core genome multilocus sequence typing; Enterococcus faecium; single nucleotide polymorphisms; ST117/CT71; ST1299/CT3109; vancomycin-resistance; wastewater

Rapid phenotypic antimicrobial susceptibility testing of Gram-negative rods directly from positive blood cultures using the novel Q-linea ASTar system - Esse, Jan; Träger, Johannes; Valenza, Giuseppe; Bogdan, Christian; Held, Jürgen (Journal of Clinical Microbiology, 2023)
Adequate and timely antibiotic therapy is crucial for the treatment of sepsis. Innovative systems, like the Q-linea ASTar, have been developed to perform rapid antimicrobial susceptibility testing (AST) directly from positive blood cultures (BCs). We conducted a prospective study to evaluate ASTar under real-life conditions with a focus on time-to-result and impact on antimicrobial therapy. Over 2 months, all positive BCs that showed Gram-negative rods upon microscopy were tested with the ASTar and our standard procedure (VITEK 2 from short-term culture). Additionally, we included multidrug-resistant Gram-negative bacteria from our archive. Both methods were compared to broth microdilution. In total, 78 bacterial strains (51 prospective and 27 archived) were tested. ASTar covered 94% of the species encountered. The categorical and essential agreement was 95.6% and 90.7%, respectively. ASTar caused 2.4% minor, 2.0% major, and 2.4% very major errors. The categorical agreement was similar to standard procedure. The average time between BC sampling and the availability of the antibiogram for the attending physician was 28 h 49 min for ASTar and 44 h 18 min for standard procedure. ASTar correctly identified all patients who required an escalation of antimicrobial therapy and 75% of those who were eligible for de-escalation. In conclusion, ASTar provided reliable AST results and significantly shortened the time to obtain an antibiogram. However, the percentage of patients that will profit from ASTar in a low-resistance setting is limited, and it is currently unclear if a change of therapy 29 h after BC sampling will have a significant impact on the patient’s prognosis.
CRIS-Team Scopus Importer:2023-12-08
Keywords: AST; blood stream infection; RAST; scum plate method; sepsis; VITEK

The Aspergillus galactomannan Ag VIRCLIA® Monotest and the sõna Aspergillus galactomannan lateral flow assay show comparable performance for the diagnosis of invasive aspergillosis - Küpper, Corinna; Erb, Timothy Moritz; Träger, Johannes; Meintker, Lisa; Valenza, Giuseppe; Bogdan, Christian; Held, Jürgen (Mycoses, 2024)
Background: Rapid galactomannan tests, such as the sõna Aspergillus GM Lateral Flow Assay (GM-LFA) and the Aspergillus Galactomannan Ag VIRCLIA® Monotest (GM-Monotest), which are suitable for the analysis of single samples, have the potential to accelerate diagnosis of invasive aspergillosis (IA). Objectives: To compare the performance of the GM-Monotest and the GM-LFA for the diagnosis of IA. Patients/Methods: Two patient cohorts were analysed: adults who had received an allogeneic haematopoietic stem-cell transplant (alloHSCT-cohort) and patients with proven/probable IA from a 5-year period (cross-sectional IA-cohort). In the alloHSCT-cohort, weekly serum samples were tested, whereas in the cross-sectional IA-cohort sera and bronchoalveolar lavage fluids were analysed. The diagnostic performance was calculated using two definitions for positivity: (1) a single positive GM result and (2) at least two positive GM results from consecutive samples. IA classification followed EORTC/MSG 2019. Results: The alloHSCT-cohort included 101 patients. Four had proven/probable IA, 26 possible IA and 71 no IA. The specificity for one positive serum and two consecutively positive sera was 88.7% and 100% (GM-Monotest) and 85.9% and 98.6% (GM-LFA). Comparison of ROC curves in the alloHSCT-cohort showed no significant difference. The cross-sectional IA-cohort included 59 patients with proven/probable IA. The sensitivity for one positive sample and two consecutively positive samples was 83.1% and 55.1% (GM-Monotest) and 86.4% and 71.4% (GM-LFA). Conclusions: Both assays showed comparable diagnostic performance with a higher sensitivity for the GM-LFA if two consecutive positive samples were required for positivity. However, due to poor reproducibility, positive GM-LFA results should always be confirmed.
CRIS-Team Scopus Importer:2024-08-16
Keywords: antigen; invasive fungal disease; invasive fungal infection; Platelia; POCT; point-of-care test